2016
DOI: 10.1016/j.jretconser.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Online purchase determinants of loyalty: The mediating effect of satisfaction in tourism

Abstract: The purpose of this research is to investigate the impact of four online purchase determinants (website image perceptions, routine, website knowledge and innovativeness) on customer loyalty and the mediating effect of customer satisfaction within the context of e-commerce. The research model is tested using data collected from 3188 regular buyers of the national leader in the sector being studied. The statistical analyses were conducted within the Structural Equation Modelling framework. Results show that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
81
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 92 publications
11
81
0
5
Order By: Relevance
“…It has been defined as a bidimensional construct that entails the result of all marketing efforts to maintain existing customers (Pereira et al 2016). Therefore, developing long-lasting relationships in the e-commerce context can be reflected in intentions to return to the website (Ku and Chen 2014) and purchase and repurchase intentions (San-Martín and Herrero 2012).…”
Section: Relational Variables In Local Food E-commercementioning
confidence: 99%
See 2 more Smart Citations
“…It has been defined as a bidimensional construct that entails the result of all marketing efforts to maintain existing customers (Pereira et al 2016). Therefore, developing long-lasting relationships in the e-commerce context can be reflected in intentions to return to the website (Ku and Chen 2014) and purchase and repurchase intentions (San-Martín and Herrero 2012).…”
Section: Relational Variables In Local Food E-commercementioning
confidence: 99%
“…In the online context, satisfaction refers to a favourable navigation experience and the perception of a well-designed website, representing also a basic key element for a successful e-commerce business relationship since it increases rate profitability and long-term sales growth in online shops Pereira et al 2016). Nevertheless, e-commerce is characterized by the absence of the physical interaction with people that leads to users' dissatisfaction due to the impersonality of the transaction (Pereira et al 2016). In this paradigm, it is very complex to generate loyalty among users.…”
Section: Relational Variables In Local Food E-commercementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly in the investigations of intangibles, a predominance of sectors such as banking (Ali and Raza 2015;Ateba, Maredza, Ohei, Deka and Schutte 2015) and tourism (Pereira, Salgueiro and Rita 2016;Triantafillidou and Petala 2016) is manifested in this type of research. Specifically within the tourism sector, the research related to this theme varies from tourism modality, with research related to health tourism (Aziz, Md-Yusof, AbuBakar, Taib and Ayob 2015), sports (Hallmann, Mueller and Peters 2015), cultural (Chai, Bao, Sun and Cao 2015) but with a large predominance of mass tourism of sun and beach (Bujosa, Riera and Pons 2015).…”
Section: Introductionmentioning
confidence: 91%
“…eWOM is defined as "the dynamic and ongoing information exchange process between potential, actual, or former consumers regarding a product, service, brand or company, which is available to a multitude of people and institutions via the Internet" (Ismagilova et al, 2017, p.18). Studies have found positive relationships between eWOM and information adoption (Chang & Wu, 2014;Wang et al, 2015), change in attitude (Hsu et al, 2013;Huang & Korfiatis, 2015;Martin & Lueg, 2013;Pan & Chiou, 2011;Shareef et al, 2018), purchase intention (Bi et al, 2017;Chen et al, 2016;Hernandez & Handan, 2014;Pappas, 2016;Pereira et al, 2016;Plotkina & Munzel, 2016;Pookulangara & Koesler, 2011;Sweeney et al, 2014;Weisstein et al, 2017) and sales of products/services (Blal & Sturman, 2014;Cadario, 2014;Eslami & Ghasemaghaei, 2018;. However, information overload from vast quantities of eWOM can cause confusion and result in a negative effect on purchase intention (Furner & Zinko, 2017;Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%